Thirty million words : building a child's brain : tune in, talk more, take turns - Suskind, Dana; Suskind, Beth; Lewinter-Suskind, Leslie (Dutton, 2015)
"The founder and director of the Thirty Million Words Initiative, Professor Dana Suskind, explains why the most important--and astoundingly simple--thing you can do for your child's future success in life is to talk to him or her, reveals the recent science behind this truth, and outlines precisely how parents can best put it into practice" --